2021
DOI: 10.1161/circinterventions.120.010296
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Ultrasound–Derived Calcium Score to Predict Stent Expansion in Severely Calcified Lesions

Abstract: Background: Coronary calcification inhibits stent expansion. We sought to establish an intravascular ultrasound–derived calcium score to predict stent underexpansion. Methods: This is a retrospective observational study including de novo lesions that underwent intravascular ultrasound–guided stenting and had maximum superficial calcium angle >270°. Lesions with angiographic calcium not treated with atherectomy or scoring/cutting balloon before stent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 22 publications
0
56
0
Order By: Relevance
“…Use of intravascular imaging can help facilitate this decision. 18,23 Zhang et al 18 In most calcified lesions noncompliant balloons (sized 1:1 to the target vessel) inflated at high pressure are initially used, followed by plaque modification balloons, atherectomy (rotational, orbital, laser), IVL, the very high-pressure balloon or extraplaque lesion crossing, and extraplaque modification. The combination of atherectomy with IVL can also be considered for both balloon uncrossable and balloon undilatable lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of intravascular imaging can help facilitate this decision. 18,23 Zhang et al 18 In most calcified lesions noncompliant balloons (sized 1:1 to the target vessel) inflated at high pressure are initially used, followed by plaque modification balloons, atherectomy (rotational, orbital, laser), IVL, the very high-pressure balloon or extraplaque lesion crossing, and extraplaque modification. The combination of atherectomy with IVL can also be considered for both balloon uncrossable and balloon undilatable lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Upfront atherectomy is preferred in heavily calcified lesions that are unlikely to respond to balloon angioplasty. Use of intravascular imaging can help facilitate this decision 18,23 . Zhang et al 18 developed an IVUS‐based calcium score with upfront use of calcium modification devices recommended in lesions with two or more of the following: (1) superficial calcium angle >270° longer than 5 mm; (2) 360° of superficial calcium; (3) calcified nodule; and (4) vessel diameter <3.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…8 A similar score has been developed for IVUS based on a >270 arc of calcium that is of >5 mm in length, vessel size of <3.5 mm (media-to-media), and presence of either circumferential calcium or a calcified nodule. 9 Stent edge problems-geographic miss, large edge dissections, or intramural hematomas-are second only to stent underexpansion as predictors of events. 10 However, even in randomized clinical trials, optimal stent implantation is seen in only half of the IVI-guided procedures.…”
Section: Stent Sizing and Optimizationmentioning
confidence: 99%
“…14 Lastly, recent intravascular imaging studies indicate that calcified nodules are more likely found in the RCA, resulting in a higher risk of stent under expansion and more adverse events compared to calcified lesions without a calcified nodule. 15,16 Although optical coherence tomography and intravascular ultrasound imaging were not tracked in this analysis, previous studies have shown that imaging optimizes and improves PCI results regardless of lesion location and ethnicity. 17,18 However, we hypothesize that patients with RCA lesions, such as the HL patients in our retrospective analysis, may especially require intravascular imaging to better characterize the calcified lesions to properly plan for vessel preparation to obtain optimal results.…”
Section: Baseline Demographic Comparison Of Hl Versus Non-hl Patientsmentioning
confidence: 99%